An Efficient Confidentiality and Integrity Preserving Aggregation Protocol in Wireless Sensor Networks. (13th February 2014) - Zhu, Liehuang; Yang, Zhen; Xue, Jingfeng; Guo, Cong
Abstract : Wireless sensor networks (WSNs) are composed of sensor nodes with limited energy which is difficult to replenish. In-network data aggregation is the main solution to minimize energy consumption and maximize network lifetime by reducing communication overhead. However, performing data aggregation while preserving data confidentiality and integrity is challenging, because adversaries can eavesdrop and modify the aggregation results easily by compromised aggregation nodes. In this paper, we propose an efficient confidentiality and integrity preserving aggregation protocol (ECIPAP) based on homomorphic encryption and result-checking mechanism. We also implement ECIPAP on SimpleWSN nodes running TinyOS. Security and performance analysis show that our protocol is quite efficient while persevering both aggregation confidentiality and integrity.